New aspects in surgery of the nasal tip - Kovacevic, M.; Wurm, Jochen (HNO, 2015)
The creation of both a functionally and aesthetically pleasing nasal tip contour is demanding and depends on a variety of parameters. Typically, procedures are performed with emphasis on narrowing the nasal tip structure. Excisional techniques alone inevitably lead to reduction in skeletal support and are often prone to unpredictable deformities. But long-term results of classical suture techniques have also shown unfavorable outcomes. Particularly pinching of the alae and displacement of the caudal margin of the lateral crus below the cephalic margin belong in this category. A characteristic loss of structural continuity between the domes and the alar lobule and an undesirable shadowing occur. These effects lead to an unnatural appearance of the nasal tip and frequently to impaired nasal breathing. Stability and configuration of the alar cartilages alone do not allow for an adequate evaluation of the nasal tip contour. Rather a three-dimensional approach is required in order to describe all nasal tip structures. Especially the rotational angle of the alar surface as well as the position of the lateral crus in relation to the cranial septum should be considered in the three-dimensional analysis. Taking the various parameters into account the authors present new aspects in nasal tip surgery which contribute to the creation of a functionally and aesthetically pleasing as well as durable nasal tip contour.
EVALuna2:19985